Oral health care in university students: hygiene habits, knowledge and self-perception to promote health (Research, Society and Development, 2022)
Objective: To investigate the behaviors, frequency and means used by university students regarding self-perception of oral hygiene, as well as the importance of care and knowledge about oral pathologies, as a strategy for the practice of a health-promoting university. Material and Methods: This is a qualitative research, which used the survey method and was carried out with university students from a private institution. As a research instrument, it consists of a questionnaire. For descriptive statistical analyses, mean, standard deviation and percentage were considered; a significant value of p ≤ 0.05 was also considered. Qualitative analyzes were presented and discussed in light of the literature on health promotion. Results: 121 university students participated in the study. With a greater predominance of students from the dentistry course, aged between 22 and 26 years and female. 50.4% say they are satisfied with their oral health; 56.2% think they currently need dental treatment; 62.8% brush their teeth 3 times a day, mostly 43% after lunch and 28.9% after dinner. 25.6% sometimes have gum bleeding when brushing their teeth. 56.2% say they sometimes use dental floss. 86.8% of participants have no impact on quality of life regarding oral health. Regarding the knowledge of oral pathologies, most participants do not have knowledge about oral pathologies. Considerations: It was possible to perceive that the level of knowledge of the participants about pathologies and pathological alterations requires attention in the dissemination of information among academics.